Digital mayhem: 3D landscape techniques : where inspiration, techniques and digital art meet - Evans, Duncan (Burlington, MA : Focal Press,Taylor Grancis Group, an inorma business, 2014)
"The secrets to creating stunning landscapes are at your fingertips with Digital Mayhem 3D Landscapes Techniques. Compiled by Duncan Evans, launch Editor of 3D Artist Magazine, Digital Mayhem features a variety of beautiful art from some of the finest digital artists working today. Inspiration and technique meet here as you learn how to create every type of landscape from harsh desert savannahs to icy tundra. Using a blend of showcase images, step-by-step and long-form tutorials, you will be guided through the featured artist's process so you can incorporate their techniques and workflow into your own projects. Not just another button-pushing manual or coffee table book, Digital Mayhem will help develop your critical eye for composition, choice of camera lens, lighting, rendering, and post production, allowing you to work more intuitively. With insight from some of the best digital artists in the world, Digital Mayhem will have you creating your own masterpiece in no time! - Unique coverage on a variety of software allows you to hone your skills across different platforms. - Illustrious and colorful artwork coupled with artist insight will both inspire and inform your creative decisions. - Comprehensive companion website offers additional resources for you to further expand your skillset"--
Includes bibliographical references and index.
Keywords: Landscape photography; Computer animation; Photography -- Digital techniques; ART / Digital